Pro-environmental Behavior in Egypt: Is there a Role for Islamic Environmental Ethics? - Rice, Gillian (Journal of business ethics, 2006)
Egypt, a less affluent, predominantly Muslim country, suffers from numerous forms of environmental pollution, some severe. This study investigates pro-environmental behaviors of citizens in Cairo, Egypt’s largest metropolis, and studies the relationship between pro-environmental behavior and demographic variables, beliefs, values, and religiosity. Analysis shows that three types of pro-environmental behavior are present: Public Sphere, Private Sphere, and Activist Behavior, with the latter occurring less frequently. Importantly, the study identifies an ecocentric value among respondents which is correlated with Public Sphere Behavior. It also confirms earlier research that characterized Egyptians’ perceptions of the environment as being set in the context of health and cleanliness. Religious teachings and religiosity are shown to be associated with pro-environmental behavior, thus lending support to the presence of an Islamic environmental ethic.